055 An atypical presentation of transient epileptic amnesia lasting six hours. (23rd August 2021) - Wood, Benjamin D; Ji, Amanda; Roizman, Michael; Swayne, Andrew
Abstract : Background: Transient epileptic amnesia (TEA) is a clinical presentation of focal epilepsy from temporal origin characterised by transient episodes of anterograde amnesia without other aspects of cognitive impairment. It is a rare diagnosis which requires evidence of epilepsy, such as epileptiform abnormalities on electroencephalogram (EEG). We present a case of a 76-year-old female with a prolonged episode of TEA. Case Description: A previously well 76-year-old female presented to a tertiary hospital emergency department following sudden onset anterograde amnesia. She was disoriented to time and had repetitive questioning, however routine physical and neurological examination revealed no abnormalities. Initial investigations including CT Head and routine bloods did not find a reversible cause for her symptoms. She subsequently fully recovered after six hours. MRI of her brain showed chronic small vessel changes with no hippocampal abnormality. Routine EEG revealed right temporal sharp waves maximal at T8, indicating an underlying temporal lobe epilepsy. A diagnosis of TEA was made, and the patient was commenced on Levetiracetam. The patient has not had further amnestic events since. Conclusion: This case demonstrates an atypical presentation of TEA. Typically, episodes of TEA last less than 1hr and occur on waking. Our case presented deceptively similarly to Transient Global Amnesia, a disorder with usually one episode of anterograde amnesia 2-24hrs long, characterized by repetitive questioning without impairment of other cognitive functions. However routine EEG workup showed evidence of temporal lobe epilepsy, re-clarifying the diagnosis as TEA. This case demonstrates the importance of EEG workup in presentations of transient amnesia.